القراءة مهارة إتقانية في العربية - Yuspa, Anida (STIT Darul Hijrah Martapura, 2024)
The Arabic language has many characteristics, too numerous to be fully listed, including phonetic features, derivation, form, structure or construction, pattern or rhythm, Arabization, brevity, and extensive meaning. With its vast literary, scientific, and cultural heritage, Arabic is considered one of the great languages of the world. Reading is an integrative skill, just like listening and understanding, requiring a visible effort from the learner during its practice. Reading is not a simple skill; rather, it is a complex process that involves a set of abilities and engages in various cognitive operations such as understanding, remembering, inferring, and evaluating. Reading remains one of the most important means of conveying the fruits of human intellect and the purest human emotions, as known in the world of printed pages. Reading has had great significance in human life since ancient times, and its importance has increased in this era due to scientific and technological advancements, as well as the explosion of knowledge in all areas of life. Humans cannot do without it, despite the availability of various means to transfer knowledge.Keyword: Reading, mastery skill, Arabic. مستخلص البحثللعربية خصائص كثيرة يضيق المجال عن حصرها، منها الخصائص الصوتية والاشتقاق والشكل والهيئة أو البناء والصيغة أو الوزن، والتعريب والإيجاز والدلالة الواسعة. وتعد اللغة العربية بتراثها الأدبي والعلمي والثقافي الضخم إحدى لغات العالم العظيمة. تعتبر القراءة مهارة استيعابية مثلها مثل الاستماع والفهم يبذل المتعلم عند ممارستها جهدًا ظاهرًا للعيان. وليست عملية القراءة من المهارات البسيطة، وإنما هي عملية معقدة تشمل مجموعة من المهارات تدخل في كثير من العمليات العقلية كالفهم والتذكر والاستنتاج والتقويم. ولا تزال القراءة أهم الوسائل التي تنقل إلينا ثمرات العقل البشري، وأنقى المشاعر الإنسانية التي عرفها عالم الصفحة المطبوعة. القراءة ذات أهمية كبرى في حياة الإنسان منذ القديم، وازدادت أهميتها في هذا العصر بسبب التطور العلمي والتكنولوجي، وتفجر المعرفة في جميع مجالات الحياة، فالإنسان لا يستغنى عنها بالرغم من وجود الوسائل المتعددة لنقل المعرفة.